ENT 530 Social Media Portfolio : Keperek Gunting Bonda / Muhammad Haikal Nadzri - Nadzri, Muhammad Haikal (2019)
This is an attempt to know how the theories can be applied to practical situation. As a student of UiTM, it is part of study for everyone to undergo Principles of Entrepreneurship (ENT530). So for this purpose, I got the opportunity of learning on how to be a successful entrepreneur. In the first part of the social media portfolio, is the business registration of the report. It is taken from Suruhanjaya Syarikat Malaysia (SSM). On the second part of the portfolio, there is the general information of the business. Other than that, the mission and vision are included in this portfolio. I also provided a description of my products. Lastly, the price list I offer to the customers. My business name is Kerepek Gunting Bonda. My product is a spicy curry taste with crunchy texture. I'm selling my product in Puncak Alam, Kajang and Semenyih area. This is my starting business from home. Currently I live in Semenyih, Selangor. Kerepek Gunting Bonda will serve to all customers who love to try something spices and crunch. The market potential for my businesses is students, kids and adults. Kerepek Gunting Bonda will offer an affordable price for customers to purchase.